1999
DOI: 10.1002/(sici)1097-0282(199909)50:3<227::aid-bip1>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of alginate beads and bound water relaxation studied by electrorotation

Abstract: The electrical and dielectric properties of Ba 2ϩ and Ca 2ϩ cross-linked alginate hydrogel beads were studied by means of single-particle electrorotation. The use of microstructured electrodes allowed the measurements to be performed over a wide range of medium conductivity from about 5 mS/m to 1 S/m. Within a conductivity range, the beads exhibited measurable electrorotation response at frequencies above 0.2 MHz with two well-resolved co-and antifield peaks. With increasing medium conductivity, both peaks shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 52 publications
(87 reference statements)
2
11
0
Order By: Relevance
“…Electrorotation studies have revealed that the aqueous environment within the capsules is completely different to that of the bulk solution. 25,26 As shown in FIGURE 7 the dispersion of water centered around 20 GHz for free water is shifted to about FIGURE 5. (A) Typical growth curves of the adherent cell line C3H10T1/2 transfected permanently with a gene encoding for bone morphogentic protein BMP-2 (similar curves were obtained for cells transfected with BMP-4).…”
Section: Performance Of Biocompatible Ba 2+ -Alginate Microcapsules Fmentioning
confidence: 92%
See 1 more Smart Citation
“…Electrorotation studies have revealed that the aqueous environment within the capsules is completely different to that of the bulk solution. 25,26 As shown in FIGURE 7 the dispersion of water centered around 20 GHz for free water is shifted to about FIGURE 5. (A) Typical growth curves of the adherent cell line C3H10T1/2 transfected permanently with a gene encoding for bone morphogentic protein BMP-2 (similar curves were obtained for cells transfected with BMP-4).…”
Section: Performance Of Biocompatible Ba 2+ -Alginate Microcapsules Fmentioning
confidence: 92%
“…Incorporation of proteins into the alginate capsules shifts the dispersion back to higher frequencies (about 106 MHz), whereas perfluorocarbons (Fluosol®) reduce the concentration of bound water as indicated by a decrease in the relative permittivity of the capsules (alginate : Fluosol ® = 1 : 1). For further details, see Esch et al 25 sules retrieved after a four-week implantation in the peritoneum of a rat show no significant changes in the topography of their surfaces ( see FIGURE 8 A). In contrast, AFM images of perfluorocarbon-alginate capsules implanted for 15 months show deposition of fibrils on their surfaces (FIG.…”
Section: Performance Of Biocompatible Ba 2+ -Alginate Microcapsules Fmentioning
confidence: 96%
“…A factor of little consideration is the property of water bound to gels such as pectins. Recent studies determining water relaxation in a model system however, suggest highly structured properties, quite different from those of free water (Esch et al , 1999). Implications for the activity of enzymes and dyes frequently used in studies on ion relations in cell walls are far from being understood.…”
Section: The Root Apoplast -Nutrient Uptake and Short-distance Tmentioning
confidence: 98%
“…In the light of the above results we can conclude that epistomatal mucilage plugs (and layers) are a widespread phenomenon. Water uptake and binding of acid mucopolysaccharides are extremely high, in particular in the presence of di-(multi-)valent cations (Morse 1990;McCully and Boyer 1977;Esch et al 1999;Zimmermann et al 2007b). This suggests that epistomatal mucilage plugs (and layers) are involved in moisture uptake and particularly in buffering the leaves against rapid and excessive turgor pressure loss at low relative humidity.…”
Section: Resultsmentioning
confidence: 99%